د ارسة مقارنة لبعض الخصائص المورفلوجية و البيوكيمائية لحبوب طلع النخيل من الصنففي منطقة واد ريغ - خلف الله خلود; بن طرية إكرام (University of Eloued جامعة الوادي, 2025)
Thistudy aims to cmpare the morpholgicalnd biochemical charcteristc of date palm polen grains from the Phoenix dactylifera L. cultivar in the Oued Righ region. The study include a morpholgicalnalysi of the polen grains uing microscpic examination, i aditon to asesing their vabilty and germination capcityn vitro. The rsults revaledifernces among the samples, withe higest viablity and germination rates recorde in the samples colectd from the municpalites of El-Zaouia El-Abida (Tougourt) and Djama (El M'Ghair),espctively. This prompted a more in-depth biochemical investigation of thes two samples. Prelimnary phytochemical tes wer conducted to detc secondary metabolites, whic showed tha both samples contained various compoundsuch as phenols, flavonids, tanis, reducing compounds, and saponis. Quantiavestimationf toal phenols and measuremnt of antioxdant activy wer also perfomed, and both samplesxhibted strong antioxdant activy. so, the study found traisn the polen grains of certain male male date palms in the Oued Righ region.
Keywords: comparison; morpholgical; biochemical; polen grains; Phoenix dactylifera L.; Oued Righ region.